2020
DOI: 10.1175/jcli-d-20-0072.1
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Convective System Precipitation Characteristics over East Asia. Part I: Regional Differences and Seasonal Variations

Abstract: Mesoscale convective systems (MCSs) play an important role in modulating the global water cycle and energy balance and frequently generate high-impact weather events. The majority of existing literature studying MCS activity over East Asia is based on specific case studies and more climatological investigations revealing the precipitation characteristics of MCSs over eastern China are keenly needed. In this study, we use an iterative rain cell tracking method to identify and track MCS precipitation during 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 60 publications
12
62
1
Order By: Relevance
“…Monsoon southerlies with a maximum near midnight tend to facilitate the early-morning rainfall systems with durations longer than 6 hours. Such a response of long-duration rainfall to wind diurnal variations is also noted in previous studies (Chen et al 2009(Chen et al , 2013Yuan et al 2010;Li et al 2020). In summary, the northward-displaced rainfall of M(+)D(+) compared with M(+)D(−) suggests that the southerly monsoon surges with different diurnal variations are closely related to the meridional movement of the monsoon rainband.…”
Section: Rainfall Response To Southerly Monsoon Surges With Different Diurnal Variations a Spatiotemporal Evolutions Of Low-level Winds Asupporting
confidence: 84%
“…Monsoon southerlies with a maximum near midnight tend to facilitate the early-morning rainfall systems with durations longer than 6 hours. Such a response of long-duration rainfall to wind diurnal variations is also noted in previous studies (Chen et al 2009(Chen et al , 2013Yuan et al 2010;Li et al 2020). In summary, the northward-displaced rainfall of M(+)D(+) compared with M(+)D(−) suggests that the southerly monsoon surges with different diurnal variations are closely related to the meridional movement of the monsoon rainband.…”
Section: Rainfall Response To Southerly Monsoon Surges With Different Diurnal Variations a Spatiotemporal Evolutions Of Low-level Winds Asupporting
confidence: 84%
“…In this study, we identify and track MCSs in space and time by using an "iterative raincell tracking (IRT)" technique (Moseley et al 2013(Moseley et al , 2019Li et al 2020b). For each time step independently, connected areas with surface precipitation exceeding a predetermined threshold are recognized as objects in the rst step.…”
Section: Iterative Raincell Tracking Methodsmentioning
confidence: 99%
“…An MCS is de ned as a single entity with intense precipitation (≥ 3.0 mm h − 1 ) covering an area larger than 3,600 km 2 , and lasting at least two hours. This threshold is set to exclude too small and non-MCS storms, thus allows us to track intense storms with relatively enough size, which follows the same threshold settings in the previous study of Li et al (2020b). Additional sensitivity tests using 5.0 mm h − 1 and 2.5 mm h − 1 have demonstrated that while the changing thresholds will impact the amount of discovered MCS, the overall MCS features remain robust and do not change the conclusions revealed in this study.…”
Section: Iterative Raincell Tracking Methodsmentioning
confidence: 99%
“…Li, Moseley, et al. (2020) found that MCS precipitation over YHRB exhibits an early morning peak in summer. The failure of numerical experiments with CPS to capture the diurnal cycle of summer rainfall over YHRB may be partly due to the difficulties of CPS to reproduce the mesoscale processes characterizing MCS.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that all simulations with different CPSs reproduced well the late-afternoon peak of precipitation, but they differed largely in the early morning peak. Li, Moseley, et al (2020) found that MCS precipitation over YHRB exhibits an early morning peak in summer. The failure of numerical experiments with CPS to capture the diurnal cycle of summer rainfall over YHRB may be partly due to the difficulties of CPS to reproduce the mesoscale processes characterizing MCS.…”
mentioning
confidence: 99%